Features of self-esteem in adolescents with different understanding of success - Darya A. Bukhalenkova; Olga A. Karabanova (Национальный психологический журнал, 2018)
Background. The paper deals with understanding success in terms of generation value gap, transitivity and high social uncertainty as a component of self-determination of an individual acquires particular relevance, determining the vector of a person’s personal development. The Objective of this research is to study the ideas of modern adolescents about success linked with self-esteem and assessment of their own success in significa nt spheres of life, i.e. education career and interpersonal relations. The study is based on the assumption that the notions of success as self-development will be associated with a higher level of self-esteem and assessment of success in adolescents. Design. The study involved 500 adolescents (291 girls and 209 young men), students of the 10th and 11th grades of schools and gymnasiums (average age 16 years), Moscow, Russia. To study the ideas of adolescents about success, Adolescent Representations of Success (ARS) questionnaire was developed. To study the self-esteem of adolescents, the method of Dembo-Rubinstein was used in the modification A.M. Prihozhan, as well as a purposefully designed questionnaire to study indirect evaluation of success. Results Three models of success that characterize the attitude of adolescents to the success are identified: success as social recognition, success as fulfillment of external social requirements, and success as self-development and self-actualization. The differences in the self-esteem of adolescents with different ideas about success are revealed. Conclusion. The research confirmed the hypothesis and showed that varying perception of success in adolescents is closely related to self-esteem and evaluation of their own success. Understanding success as self-development and self-actualization is associated with a higher level of self-esteem and assessment of own success which promotes psychological well-being in general. Adolescents who share a model of success as fulfillment of external social requirements associate success with achieving goals with overcoming obstacles and satisfaction with results and place value on luck. For adolescents who are focused on the model of success as social recognition it is typical to place value on their personal authority among the peers, thus having high assessment rates of their success as a whole.